Better Response to Influenza Virus Vaccination in Physically Trained Older Adults Is Associated With Reductions of Cytomegalovirus-Specific Immunoglobulins as Well as Improvements in the Inflammatory and CD8+ T-Cell Profiles - Felismino, Eduardo S.; Santos, Juliana M. B.; Rossi, Marcelo; Santos, Carlos A. F.; Durigon, Edison L.; Oliveira, Danielle B. L.; Thomazelli, Luciano M.; Monteiro, Fernanda R.; Sperandio, Adriane; Apostólico, Juliana S.; França, Carolina N.; Amaral, Jonatas B.; et al. (Frontiers in Immunology, 2021)
Chronic cytomegalovirus (CMV) infection is a trigger factor for the development of immunosenescence and negatively impacts the immune response to influenza virus vaccination (IVV) in older adults. However, the role of physical exercise training in this context is unknown. Thus, the aim of this study was to investigate whether the regular practice of combined exercise training can improve the specific antibody response to IVV in CMV-seropositive older adults. Eighty older adults were distributed into two groups—non-practitioners (NP, n = 31, age = 74.06 ± 6.4 years) and practitioners of combined exercise training (CET, n = 49, age = 71.7 ± 5.8 years)—for at least 12 months. Both volunteer groups were submitted to IVV and blood samples were collected before (pre) and 30 days after (post) the vaccination. Concerning the specific antibody response to IVV, higher serum levels of specific immunoglobulin A (IgA) were found in the CET group post- than pre-vaccination (p < 0.01), whereas higher levels of specific immunoglobulin M (IgM) were observed both in the NP (p < 0.05) and CET (p < 0.001) groups post-vaccination as compared to the pre-vaccination values. Serum levels of specific immunoglobulin G (IgG) for IVV and CMV, as well as interleukin 6 (IL-6) and IL-10, were similar between the time points evaluated. However, the IL-10/IL-6 ratio post-vaccination was higher (p < 0.05) in the CET group than that before vaccination. Negative correlations were observed between the specific IgG levels for IVV and CMV only in the CET group, both pre- and post-vaccination. In addition, negative correlations were found between IL-10 and specific IgG for CMV in all volunteer groups pre- and post-vaccination, whereas a positive correlation between IL-10 and specific-IgG for IVV pre- and post-vaccination was observed in the CET group. In addition, with the hemagglutination inhibition (HAI) assay, it was found that 32.2% of the NP group and 32.6% of the CET group were responders to IVV and displayed reductions in the CMV serostatus (p < 0.05 and p < 0.001, respectively) and increases in naive and effector CD8+ T cells post-vaccination (p < 0.01). However, only the responders from the CET group showed significant reductions in the ratio of effector to naive CD8+ T cells (p < 0.05) and increased IL-10 levels post-vaccination (p < 0.001). In summary, this study demonstrates that the improvement in the response to IVV in CMV-seropositive older adults was related to an anti-inflammatory status and enhancement of naive CD8+ T cells, particularly associated with regular practice of CET.